2012
DOI: 10.1371/journal.pone.0041658
|View full text |Cite
|
Sign up to set email alerts
|

Blood Lymphocyte-to-Monocyte Ratio Identifies High-Risk Patients in Diffuse Large B-Cell Lymphoma Treated with R-CHOP

Abstract: BackgroundRecent research has shown a correlation between immune microenvironment and lymphoma biology. This study aims to investigate the prognostic significance of the immunologically relevant lymphocyte-to-monocyte ratio (LMR), in diffuse large B-cell lymphoma (DLBCL) in the rituximab era.Methodology/Principal FindingsWe analyzed retrospective data from 438 newly diagnosed DLBCL patients treated with rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) therapy. We randomly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
109
6
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(129 citation statements)
references
References 33 publications
13
109
6
1
Order By: Relevance
“…17 These peripheral blood monocytes suppress host immunity by inhibiting the proliferative ability of interferon-γ, impairing the differentiation ability of dendritic cells. 1 In this study, however, the impact of AMC was still significant even after adjusting for systemic relapse as a timedependent covariate. In addition, among patients who developed systemic relapse, the incidence of subsequent CNS relapse was significantly higher in patients with high AMC at diagnosis.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…17 These peripheral blood monocytes suppress host immunity by inhibiting the proliferative ability of interferon-γ, impairing the differentiation ability of dendritic cells. 1 In this study, however, the impact of AMC was still significant even after adjusting for systemic relapse as a timedependent covariate. In addition, among patients who developed systemic relapse, the incidence of subsequent CNS relapse was significantly higher in patients with high AMC at diagnosis.…”
Section: Discussioncontrasting
confidence: 60%
“…DLBCL accounts for 25-30% of non-Hodgkin lymphomas among adults in the west, and it is even more prevalent in developing countries. 1 In Japan, it was reported that DLBCL is the most frequent subtype and accounts for over 30% of cases of non-Hodgkin lymphomas among adults. 2 Central nervous system (CNS) involvement is not common in DLBCL, but several risk factors for CNS involvement have been identified, including high International Prognostic Index score, involvement of more than one extranodal site, elevated lactate dehydrogenase level, poor Eastern Cooperative Oncology Group performance status (PS), advanced stage, and involvement of bone marrow, breast, testis, retroperitoneal lymph nodes, orbit, or epidural space.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are in line with previously published studies from hematological cancer. 15,16,25 Furthermore, supplementing the Kattan nomogram by the L/M ratio improved the predictive ability …”
Section: Discussionmentioning
confidence: 99%
“…8 Another study showed a correlation between low L/M ratio and poor survival in diffuse large B-cell lymphoma patients. 25 In patients with metastatic melanoma, elevated monocyte counts in peripheral blood were associated with poor survival. 26 In our study, we found a statistically significant association between a low L/ M ratio and CCS and DFS in STS patients in univariate as well as multivariate analysis for both data sets.…”
Section: Discussionmentioning
confidence: 99%
“…In the non-immunosuppressed, DLBCL biopsies display features of a host immune response, including genes and proteins associated with lymphocytes and monocytes [10][11][12][13]. In this respect, recent studies have demonstrated circulating immune cells measured by the complete blood counts (CBC), such as absolute lymphocyte counts (ALC) and absolute monocyte counts (AMC), either alone or in combination with each (e.g., lymphocyte/monocyte ratio: LMR), predict outcome independent of the R-IPI [14][15][16].…”
Section: Introductionmentioning
confidence: 99%